Motivating students with learning disabilities: fostering lifelong readers - Krueger, Gina M. (My University, 2011)
In recent years motivation has been added as a critical component in literacy. Some students are motivated more than others. Students with learning disabilities typically are less motivated. Research has shown that this is in part due to students with learning disabilities tending to have characteristics that contribute to low motivation to read. The goal of this capstone aimed to research motivation and strategies to increase motivation in terms of reading.
Keywords: Learning disabilities; Literacy